Radiological Evaluation of Penetration of the Irrigant according to Three Endodontic Irrigation Techniques - Said Dhaimy; Sara Imdary; Sara Dhoum; Imane Benkiran; Amal El Ouazzani (Hindawi Limited, 2016)
Introduction. This experimental study is to compare radiographs based on the penetration depth of the irrigant following three final irrigation techniques. Material and Method. A sample of sixty teeth with single roots were prepared with stainless steel K files followed by mechanized Ni-Ti files iRace® under irrigation with 2.5% sodium hypochlorite. Radiopaque solution was utilized to measure the penetration depth of the irrigant. Three irrigation techniques were performed during this study: (i) passive irrigation, (ii) manually activated irrigation, and (iii) passive irrigation with an endodontic needle CANAL CLEAN®. Radiographs were performed to measure the length of irrigant penetration in each technique. Results. In comparison, passive irrigation with a conventional syringe showed infiltration of the irrigant by an average of 0.682±0.105, whereas the manually activated irrigation technique indicated an average of 0.876±0.066 infiltration. Irrigation with an endodontic syringe showed an average infiltration of 0.910±0.043. The results revealed highly significant difference between the three irrigation techniques (α=5%). Conclusion. Adding manual activation to the irrigant improved the result by 20%. This study indicates that passive irrigation with an endodontic needle has proved to be the most effective irrigation technique of the canal system.